Global development : a cold war history - Lorenzini, Sara 1974- (America in the world, 2019)
In the Cold War, "development" was a catchphrase that came to signify progress, modernity, and economic growth. Development aid was closely aligned with the security concerns of the great powers, for whom infrastructure and development projects were ideological tools for conquering hearts and minds around the globe, from Europe and Africa to Asia and Latin America. In this sweeping and incisive book, Sara Lorenzini provides a global history of development, drawing on a wealth of archival evidence to offer a panoramic and multifaceted portrait of a Cold War phenomenon that transformed the modern world.Taking readers from the aftermath of the Second World War to the tearing down of the Berlin Wall, Lorenzini shows how development projects altered local realities, transnational interactions, and even ideas about development itself. She shines new light on the international organizations behind these initiatives—examining their strategies and priorities and assessing the actual results on the ground—and she also gives voice to the recipients of development aid. Lorenzini shows how the Cold War shaped the global ambitions of development on both sides of the Iron Curtain, and how international organizations promoted an unrealistically harmonious vision of development that did not reflect local and international differences. An unparalleled journey into the political, intellectual, and economic history of the twentieth century, this book presents a global perspective on Cold War development, demonstrating how its impacts are still being felt today